Respuesta :

Answer:

B


Step-by-step explanation:

Let's multiply this out and combine like terms:

[tex]3x(x+1)+x\\=3x^2+3x+x\\=3x^2+4x[/tex]


So there are 2 terms.

Answer choice B is right.

Answer:

B. 2

Step-by-step explanation:

we are given

[tex]3x(x+1)+x[/tex]

Firstly, we will distribute 3x

[tex]a(b+c)=a\times b+a\times c[/tex]

we can use this formula

and we get

[tex]3x(x+1)+x=3x\times x+3x\times 1+x[/tex]

[tex]3x(x+1)+x=3x^2+3x+x[/tex]

now, we can combine like terms

[tex]3x(x+1)+x=3x^2+4x[/tex]

we can see that there are two terms after simplifying

so, there are two terms

option-B